Effect of Saccharomyces cerevisiae and Lactobacillus acidophilus on Biochemical parameters of Barbari kids (Indian Journal of Animal Production and Management, 2016)
The present study was conducted on Barbari kids to assess the effect of probiotics supplementation on  biochemical parameters. A total 18 Barbari kids were selected and randomly distributed in three groups. The  1st group (T1, n=6) was kept control fed (basal ration) without supplementation, the group 2nd (T2,n=6) was  supplemented with Lactobacillus acidophillus @ 2g/animal/day and group 3rd (T3, n=6) was supplemented  with Saccharomyces cerevisiae @ 2g/animal/day. Higher serum blood glucose, total protein and albumin  level was observed at monthly interval in probiotics supplemented group as compared to unsupplemented  group. Lower serum cholesterol level was observed in supplemented group T2 and T3 as compared to  control group T1.
Keywords: Barbari kids; Biochemical parameters; Probiotics; Supplementation